Shape Memory Alloys 2020 - Lopez, Gabriel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Shape memory alloys (SMAs), in comparison with other materials, have the exceptional ability to change their properties, structure, and functionality depending on the thermal, magnetic, and/or stress fields applied. As is well known, in recent decades, the development of SMAs has allowed innovative solutions and alternatives in biomedical applications and advanced engineering structures for aerospace and automotive industries as well as in sensor and actuation systems, among other sectors. Irrespective of this, designing and engineering using these special smart materials requires a solid background in materials science in order to consolidate their importance in these fields and to broaden their relevance for other new applications. The goal of this Special Issue is to foster the dissemination of some of the latest research devoted to these special materials from different perspectives.